Analysis of the Relationship between the Level of Community Participation and the Effectiveness of Adaptive Governance in the Coastal Area of ​​Cebu - Maria Angelica Reyes (Adaptive Governance Research, 2024)
Purpose: This study aims to analyze the relationship between community participation and the effectiveness of adaptive governance in the coastal areas of Cebu, Philippines, with a focus on socio-demographic, institutional, and socio-economic factors influencing engagement. Subjects and Methods: A mixed-methods approach was employed, combining survey data from 200 coastal households with semi-structured interviews involving key stakeholders. Quantitative data were analyzed using descriptive statistics, cross-tabulation, and logistic regression, while qualitative data were examined through thematic analysis. Results: The findings show that awareness of coastal policies is relatively high, but participation and decision-making involvement remain moderate. Education, fishing dependency, and policy awareness significantly influence participation, with awareness emerging as the strongest predictor. Conclusions: Governance is perceived as moderately effective, with positive environmental outcomes but limitations in inclusiveness and responsiveness. Adaptive governance is shaped by both structural factors and social dynamics, indicating the need for more inclusive, participatory, and responsive governance systems.